2013
DOI: 10.1063/1.4826355
|View full text |Cite
|
Sign up to set email alerts
|

The velocity operator in quantum mechanics in noncommutative space

Abstract: We tested in the framework of quantum mechanics the consequences of a noncommutative (NC from now on) coordinates. We restricted ourselves to 3D rotationally invariant NC configuration spaces with dynamics specified by the Hamiltonian H = H(kin) + U, H(kin) is an analogue of kinetic energy and U = U(r) denotes an arbitrary rotationally invariant potential. We introduced the velocity operator by Heisenberg relation using the commutator of the coordinate and the Hamiltonian operators. We found that the NC veloci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 19 publications
3
36
0
1
Order By: Relevance
“…where the +1 was added to ensure that r 2 − x 2 i = O(λ 2 ) (so there is no term linear in λ). This construction of 3D rotational invariant space R 3 λ was developed in [4] and explored by the present authors and their collaborator in [5,6,7,8,9,10,11].…”
Section: Introductionmentioning
confidence: 98%
“…where the +1 was added to ensure that r 2 − x 2 i = O(λ 2 ) (so there is no term linear in λ). This construction of 3D rotational invariant space R 3 λ was developed in [4] and explored by the present authors and their collaborator in [5,6,7,8,9,10,11].…”
Section: Introductionmentioning
confidence: 98%
“…Even though we find the succession presented in this report more logical, the historical order is that we analyzed NC QM first, see [17,18,19,20], then found out the generalization introducing the monopoles, see [21,22], and considered the commutative theory only afterward, see [23]. The outlook, for now, is to utilize the found symmetries and consider the relativistic generalization of the theory.…”
Section: Discussionmentioning
confidence: 92%
“…Preserving the rotational symmetry has many advantages, for example, the Hydrogen atom problem remains exactly solvable, see [18]. Study of the velocity operators [17] revealed how the UV cut-off manifest itself in terms of higher symmetry (SO(4) instead of the expected SO (3)).…”
Section: Noncommutative Quantum Mechanicsmentioning
confidence: 99%
“…[86]). The above space has an SO(4) symmetry [87], which one would gauge. In this procedure, the need of including additional generators emerges, typical in non-Abelian non-commutative gauge theories, for the anticommutators to close.…”
Section: −Dimensional Gravity As a Gauge Theory On Non-commutative Smentioning
confidence: 99%